Strategi Pemasaran Pangan Pokok Potensial (ubi-ubian) pada masyarakat Suku Arfak di Kampung Warmare. - Christin Haurissa, Julin; Sadiyah, Siti Halimatus; Wibowo, Kunto (Program Pascasarjana Universitas Papua, 2026)
ABSTRACT : This study aims to identify the factors that constitute strengths, weaknesses, opportunities, and threats in the marketing of tuber crops, as well as to determine effective strategies for marketing tuber commodities produced by the Arfak Tribe in Warmare Village. The main problems faced include farmers’ low understanding of marketing, limited market access, and price competition. This study employs a descriptive approach using a case study method with SWOT analysis. The results indicate that the strengths lie in more than 10 years of marketing experience, while the weaknesses are reflected in low production volumes. Opportunities are identified in the relatively high market prices of tubers, ranging from IDR 21,000 to IDR 30,000 per kilogram, whereas threats arise from intense competition from producers who cultivate three to four types of tubers. The study also found that chip-processing industries purchase raw materials from Nenei Village, South Manokwari, due to the insufficient supply of tuber products in Manokwari Regency. The findings place this study in Quadrant I, which supports an aggressive strategy and emphasizes the SO (Strengths–Opportunities) strategy, namely: (a) providing training in tuber cultivation, technological support for production facilities; and (b) establishing farmer group–based cooperatives to strengthen farmers’ price bargaining power and expand marketing distribution networks.